Correlation Between Maternal Serum Concentrations of Mannose-Binding Lectin and The Risk of Shorter Duration of Pregnancy and Lower Birth Weight - Pinar Maher Khalifa; Zuhud M. Mustafa (Zien Journals, 2022)
The aim of this study is to investigate whether serum concentrations of MBL correlate with the incidence of preterm birth and low birth weight in a cohort of women with signs of threatened preterm birth
Keywords: Mannose-Binding Lectin; Preterm labor; Lower Birth Weight